القواعد الشرعية وتطبيقاتها الفقهيَّة في ميدان العمل الخيري (El-Wahat Journal for Research and Studies, 2025)
This researchtried to collect the most important  jurisprudential (fiqhrules) and purposesrulesthat guide charity and volunteeringworkwhichshouldbeunderits control and guidance in ordre to be more organizedrationalized in suchwaywill gain its objectives and purposes, thereforethisstudywilldefine the twokind of rules (fiqh&purposes) also deals withcharityworkdefinitionthen look atthoserules subdivision fiqh cases. My main problematic in thisresearchis to explain the most important fiqh and purposesrulesthatshouldguidcharity and volunteeringwork.The researchconcludedthat for the success of charitable work and the achievement of its goals and objectives, it must beregulated by Sharia rules and controls, otherwiseitwouldbecontrary to the purposes of the law. It bringsbenefits and increasesthem, and prevents and reducesharms, and does not achieve the resultsexpectedfromit. Key words: fiqh rules, purposes rules, charity & volunteering work.